Frogs - Driscoll, Laura; Moffatt, Judith (Penguin Young Readers, an imprint of Penguin Group (USA) Inc. New York, New York, 2011)
An introduction to amphibians as tiny as a fingertip or as large as a foot whose tails little by little shrink and disappear